2019
DOI: 10.4067/s0718-27242019000300072
|View full text |Cite
|
Sign up to set email alerts
|

E-Commerce C2C en Chile: Incorporación de La Reputación y de la Confianza en El TAM

Abstract: E-commerce in Chile has been growing considerably in recent years. However, it is still far from reach its full potential. Considering the benefits that e-commerce offers to small and medium companies to improve their competitiveness on a global scale, it is essential to improve our understanding about the factors that could encourage the use of this digital shopping channel. In this research we adopted the Technology Acceptance Model (TAM) as the basis for analyzing Consumer-to-Consumer (C2C) e-commerce in Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 40 publications
(52 reference statements)
5
10
0
1
Order By: Relevance
“…Moslehpour et al (2018) identified that Taiwanese online consumers who perceive technology as a valuable tool for shopping online tend to make more online purchases. Sukno and Riquelme (2019) found similar results in C2C e-commerce in Chile. Ventre and Kolbe (2020) identify the perceived usefulness of online reviews as the essential factor in online shopping intention for Mexican consumers aged 18 to 50 years old who use e-commerce.…”
Section: Perceived Usefulnesssupporting
confidence: 71%
See 3 more Smart Citations
“…Moslehpour et al (2018) identified that Taiwanese online consumers who perceive technology as a valuable tool for shopping online tend to make more online purchases. Sukno and Riquelme (2019) found similar results in C2C e-commerce in Chile. Ventre and Kolbe (2020) identify the perceived usefulness of online reviews as the essential factor in online shopping intention for Mexican consumers aged 18 to 50 years old who use e-commerce.…”
Section: Perceived Usefulnesssupporting
confidence: 71%
“…Previous research also suggested a positive relationship between perceived ease of use and perceived usefulness (e.g., Çelik and Yilmaz 2011;Kim 2012;Manis and Choi 2019;Sukno and Riquelme 2019). However, the empirical results may differ, suggesting that the effect of perceived ease of use on perceived usefulness and purchase intention may be different according to the context and technology researched (Isaac et al 2017).…”
Section: Perceived Ease Of Purchasementioning
confidence: 92%
See 2 more Smart Citations
“…Asimismo, (Sukno & Pascual-del-Riquelme, 2019) demuestran que hay una correlación positiva entre la facilidad del uso de una plataforma con la confianza que pueda desarrollar el consumidor frente a la empresa. En cuanto al estudio de (Perdigón-Llanes, et al 2018), se muestra que el posicionamiento del negocio en los buscadores web, la correcta selección de los canales de comunicación con los clientes mejorará la interacción que tenga la empresa con los clientes.…”
Section: Discussionunclassified